The view from nowhere - Nagel, Thomas, 1937- (Oxford University Press, 1986)
Human beings have the unique ability to view the world in a detached way: We can think about the world in terms that transcend our own experience or interest, and consider the world from a vantage point that is, in Nagel's words, ""nowhere in particular"". At the same time, each of us is a particular person in a particular place, each with his own ""personal"" view of the world, a view that we can recognize as just one aspect of the whole. How do we reconcile these two standpoints--intellectually, morally, and practically? To what extent are they irreconcilable and to what extent can they be integrated? Thomas Nagel's ambitious and lively book tackles this fundamental issue, arguing that our divided nature is the root of a whole range of philosophical problems, touching, as it does, every aspect of human life